Flaplessly placed 2.4-mm mini-implants for maxillary overdentures: a prospective multicentre clinical cohort study. Issue 3 (March 2020) - Van Doorne, L.; De Kock, L.; De Moor, A.; Shtino, R.; Bronkhorst, E.; Meijer, G.; De Bruyn, H.
Abstract: Studies on flaplessly placed, one-piece mini dental implants (MDIs) supporting overdentures in the maxilla are scarce. This prospective multicenter cohort study evaluated the outcomes (over 2 years) of five to six MDIs placed in the maxilla for overdentures. Study patients were ≥50 years old, with an edentulous maxilla and dentate/fixed prosthesis in the mandible. Dentures were provisionalized with the final connection at 6 months. Implant/prosthetic survival was evaluated, and postoperative discomfort and patient satisfaction were assessed (rating scale). Of 185 MDIs placed in 31 patients, 32 failed in 16 patients (17.3%); 22/83 in female patients and 10/102 in male patients. Kaplan–Meier analysis showed survival percentages of 86.3% (6 months), 84.0% (1 year), and 82.3% (2 years). Two patients lost five or six MDIs resulting in two prosthetic failures (6.5%). Implant loss was significantly affected by sex, but not by smoking or location. The worst treatment combination was a torque value >25 N·cm with an antagonist implant overdenture. The mean pain score was 4.1 ± 2.8 on day 1 and 1.1 ± 1.7 on day 7. The mean final satisfaction score was 8.6 ± 1.7. The majority (96%) of the patients would recommend this treatment. Despite higher MDI failure in the maxilla compared to the mandible, prosthetic survival was acceptable and patient satisfaction was high, suggesting this to be a valuable treatment alternative.